Celično staranje - Dahmane, Raja (Obzornik zdravstvene nege, 2006)
Ageing can be defined as a progressive failure of body homeostasis in the absence of illness, trauma or their consequences. Age-related-changes are a reduced tolerance to stress, a reduced functional reserve of individual organsand an impaired metabolism of proteins, lipids and carbohydrates, DNA and RNA on a cellular level. The two key challenges of studying age-related-changes are the distinction between cause and effect, and the detection of age-related-changes that have an important impact on life expectancy. In human, the aging process can be attenuated by reducing oxidative stress in the body - by the ingestion of antioxidants or caloric restriction.
Keywords: celice; celično staranje; oksidativni stres; staranje